Tendon Stem/Progenitor Cells and Their Interactions with Extracellular Matrix and Mechanical Loading - Chuanxin Zhang; Jun Zhu; Yiqin Zhou; Bhavani P. Thampatty; James H-C. Wang (Stem Cells International)
Tendons are unique connective tissues in the sense that their biological properties are largely determined by their tendon-specific stem cells, extracellular matrix (ECM) surrounding the stem cells, mechanical loading conditions placed on the tendon, and the complex interactions among them. This review is aimed at providing an overview of recent advances in the identification and characterization of tendon stem/progenitor cells (TSPCs) and their interactions with ECM and mechanical loading. In addition, the effects of such interactions on the maintenance of tendon homeostasis and the initiation of tendon pathological conditions are discussed. Moreover, the challenges in further investigations of TSPC mechanobiology in vitro and in vivo are outlined. Finally, future research efforts are suggested, which include using specific gene knockout models and single-cell transcription profiling to enable a broad and deep understanding of the physiology and pathophysiology of tendons.